General aspects about Allium sativum - a review - Loría Gutiérrez, Arlene (2021)
Introduction: Garlic has been used as a food and medicinal plant through the years. Antimicrobial, antiviral, and immunostimulatory effects are attributed to garlic, so it is widely recommended to treat diseases like asthma, bronchitis, influenza, and some others. Method: This work’s objective was to conduct a literature review and analysis related to garlic medicinal-use, and it’s potential as a therapeutic agent and immunostimulant in different diseases and health conditions. The literature review was carried out in the databases Scielo, Clinical Key, Medline and ClinicalTrials.gov, among others. Results: The information consulted supports the health benefits associated with garlic consumption. The crushing of garlic bulbs allows obtaining alliin, which turns into allicin due to enzymatic oxidation. This compound has a fundamental role in the garlic’s medicinal properties, and the garlic plant’s activity depends on its ability to produce allicin. Preclinical studies have shown the improvement of the immune system, and specific proteins associated with its immunostimulating effect have been identified. In clinical studies, supplements with garlic derivatives have been administered to patients, and a decrease in the incidence of influenza and acute respiratory diseases has been observed. Conclusions: Garlic has been shown to have a significant clinical potential to treat many diseases, and immunomodulatory effects and viral acute respiratory disease prevention have been observed.